Tourism and gender : embodiment, sensuality and experience - Pritchard, Annette (CABI, 2007)
These studies seek to advance feminist and gender tourism studies with its focus on embodiment. Broad themes include the construction of narratives, how discourses of desire, sensuality and sexuality pervade the tourism experience, and how travel and tourism allow for empowerment, resistance and carnivalesque opportunities.